Combined effect of Acupuncture and Hot Foot Bath on tension type headache among young adults: A randomized control trial - Murthy P, Ranjini; AN, Vineetha; MK, Nitesh; -, Lakshmeesha; Ragavendrasamy, Balakrishna; HM, Prajwal; CN, Shravya; S, Swathi; T, Vinaya Kumar (Indian Journal of Integrative Medicine, 2024)
Background & Objectives: Tension type headache (TTH) is the third most common disease worldwide causing physical and mental suffering. The main cause is the central sensitization, myofascial triggers, neuromuscular changes that lead to increased activity and muscle tension. The main objective of the study was to evaluate the efficacy of acupuncture and hot foot bath in alleviating the symptoms associated with TTH. Materials & Methods: A total of 90 participants (18-26 years) with headaches were screened. Out of these, 60 met the inclusion and diagnostic criteria and randomly divided into two groups using coin toss method. Pre- assessments such as Visual Analog Scale (VAS), Headache Disability Index (HDI), and Pain Disability Index (PDI) were performed before treatment. For 10 days, acupuncture was given for 30 min. in the morning, and a hot foot bath was given for 20 min. in the evening. Post- assessments were conducted at the end of the 10th day. All the details of the study were explained and informed consent was obtained from the subjects. Results: In the present study Paired sample t-test for within group changes showed a significant difference in all parameter (VAS, HDI, PDI) when compared within the group and control group with level of significance p≤0.05. Reduction noticed in control group in the absence of appropriate intervention may be due to consumption of analgesics on severe attacks. Between group changes performed using analysis of covariance for variables of interest adjusted for their respective baseline values indicated a significant difference in all parameter (VAS, HDI, PDI). Conclusion: Following the 10-days intervention, it was concluded that acupuncture and hot foot bath were found effective for treatment of TTH as demonstrated by significant differences in VAS, HDI, and PDI both before and after the treatment with p≤0.05.